Dangerous goods unit Penang Port Commission (PPC) / Siti Suhainis Md Zain - Md Zain, Siti Suhainis (2015)
Status of declaration dangerous goods is important before the activities of loading, discharge or transshipment in the port to be carried out. The dangerous goods to be declared accordingly to the port authorities 48 hours in advance arrival. So, a study was a conducted to determinants for status of declaration dangerous goods arrival at Penang Port. The secondary data was used in the study and the population of study is all the port users do the activities of dangerous goods in the port. From the population, only port users do the activities in the Penang Port is selected as sample. The total data selected was 286 respondents (port users) from population data. The method use to analyses the data is using chi square test to describe the relationship between container size, type of port users, weight of dangerous goods, total weight of dangerous goods, number of container and status of declaration dangerous goods. Based on chi square results only container size (20 footer) and weight of dangerous goods is significant with p-value less than 0.05. The significant variable is use multiple binary logistic regression using backward selection method to determine factors of status of declaration dangerous goods. The analysis shows that the factors of status of declaration dangerous goods are container size and weight of dangerous goods